Bradyrhizobium Inoculation of Field-Grown Kersting's Groundnut [Macrotyloma geocarpum (Harms) Marechal & Baudet] Increased Grain Yield and N2 Fixation, Measured Using the Ureide, and 15N Natural Abundance Techniques - Mohammed, Mustapha; Mbah, Glory C.; Sowley, Elias N. K.; Dakora, Felix D. (Frontiers in Sustainable Food Systems, 2021)
Here, we report on the symbiotic N2 fixation and water use efficiency (δ13C) of Kersting's groundnut, an important but underutilized grain legume in Africa, in response to inoculation with Bradyrhizobium strains 3267 and CB756. The 15N natural abundance and xylem ureide techniques were used to quantify N2 fixation. The landraces in this study derived variable levels of their N requirements from symbiosis, which translated into marked differences in the amounts of N-fixed by the landrace–inoculant combinations across the test locations. In most instances, the landrace-strain combinations that elicited higher shoot biomass also recorded greater N-fixed and/or ureide-N in xylem sap as well as grain yield. Although some landraces coupled increased grain yield with higher water use efficiency (shoot δ13C), a trait that could be tapped for crop improvement, others recorded lower yields despite eliciting relatively high shoot δ13C values, indicating genotypic variations in adaptation to the different environments. Grain yield of the test landraces showed marked variation and ranged from 131 to 1349.8 kg ha−1 depending on the landrace–strain combination used and the planting location. The high symbiotic dependence by landraces in this study could explain why Kersting's groundnut thrives in the low nutrient soils that are prevalent in its cultivation areas. These results provide more insights into the literature regarding the Kersting's groundnut–rhizobia symbiosis as well as the crop's water use efficiency.